THE REPRESENTATION OF CHINESE SOCIETY AS PORTRAYED IN IP MAN 4: THE FINALE MOVIE - Marlborizky Dyah Maharanie Wahyono; Nita Maya Valiantien; Aries Utomo (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This article discussed the representation of Chinese society as portrayed in IP Man 4: The Finale movie. Furthermore, the representation of the Other towards the Chinese character using Macfie's representation theory, while Murphy's characterization theory was used to analyze the struggle waged by the Chinese society. The reasons the researcher chose this movie, because (1) IP Man 4: The Finale movie is one of the movies that have just aired in 2020, (2) no one has analyzed this movie using representation theory, and (3) also until now there are still many cases where there are still superiority and inferiority between East and West that still exist and cannot be solved. In this research, the research design used was qualitative by using a qualitative descriptive analysis approach. This research reveals that the representation of Chinese society in IP Man 4: The Finale movie is aberrant, despotic, inferior, passive, feminine, backward, and inauthentic. The findings show that the struggle of Chinese society was characterized by three significant ways, namely: The past life (the character's past story), the character's speech (conversation and mind), and mannerism (reaction or action). By looking at representation theory, we can understand that the term oriental culture aims to prevent the East from not getting a negative connotation. This term is not a justification for blaming something that inaccurate statement, but rather an effort to keep the Eastern nation honorable and dignified.